Rag GTPase-mediated regulation of mTORC1 by nutrients is necessary for neonatal autophagy and survival - Efeyan, Alejo (2012)
The mTOR Complex 1 (mTORC1) pathway regulates organismal growth in response to many environmental cues, including nutrients and growth factors(1). Cell-based studies showed that mTORC1 senses amino acids through the Rag family of GTPases (2,3), but their importance in mammalian physiology is unknown. Here, we generated knock-in mice that express a constitutively active form of RagA (RagA(GTP)) from its endogenous promoter. RagA(GTP/GTP) mice develop normally, but fail to survive postnatal day 1. When delivered by Caesarian-section, fasted RagA(GTP/GTP) neonates die almost twice as rapidly as wild-type littermates. Within an hour of birth, wild-type neonates strongly inhibit mTORC1, which coincides with profound hypoglycaemia and a drop in plasma amino acid levels. In contrast, mTORC1 inhibition does not occur in RagA(GTP/GTP) neonates, despite identical reductions in blood nutrient levels. With prolonged fasting, wild-type neonates recover their plasma glucose levels, but RagA(GTP/GTP) mice remain hypoglycaemic until death, despite using glycogen at a faster rate. The glucose homeostasis defect correlates with the inability of fasted RagA(GTP/GTP) neonates to trigger autophagy and produce amino acids for de novo glucose production. Because profound hypoglycaemia does not inhibit mTORC1 in RagA(GTP/GTP) neonates, we hypothesized that the Rag pathway signals glucose as well as amino acid sufficiency to mTORC1. Indeed, mTORC1 is resistant to glucose deprivation in RagA(GTP/GTP) fibroblasts, and glucose, like amino acids, controls its recruitment to the lysosomal surface, the site of mTORC1 activation. Thus, the Rag GTPases signal glucose and amino acid levels to mTORC1, and play an unexpectedly key role in neonates in autophagy induction and thus nutrient homeostasis and viability.